Assessment of Physical Fitness Learning Objectives Using the Indonesian Student Fitness Test Instrument For Phase D Students - Fudin, Muhammad Soleh (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2023)
The aims of this research include 1) to find out the physical fitness level of Phase D students at SMPN 2 Tugu; 2) to find out the results of the assessment of the physical fitness learning objectives of Phase D students at SMPN 2 Tugu; 3) to find out what the percentage of completion is and how to follow up on the results of the assessment of the physical fitness learning objectives of Phase D students at SMPN 2 Tugu. This research is quantitative research with descriptive methods. The sample for this research is phase D students at SMPN 2 Tugu. The sample for this research was determined using a purposive sampling technique so that the research sample totaled 503 students. Meanwhile, the analysis technique uses descriptive statistics. The conclusions in this research include that the physical fitness level of phase D students at SMPN 2 Tugu is mostly categorized as poor because students do not understand the importance of physical fitness in daily activities. The results of the assessment of physical fitness learning objectives carried out for the most part have not achieved completeness. Completeness in assessing learning objectives depends on the value interval determined by the teacher or educational unit. The results of completing learning objectives as a follow-up process to improve the learning process and evaluate learning objectives.